Craighead family ledger - Craighead family
Ledger of the Craighead family, owners of Stonewall, a plantation located in Mississippi County, Ark. Consists of lists of slaves, family genealogy, medical prescriptions and recipes, accounts of the slaughter of hogs and heifers, speeches and court testimony by family members, and miscellaneous diary entries. The accounts were kept primarily by or for James B. Craighead during the 1840s and 1850s. Includes a typewritten transcript of a portion of the ledger.
Southern plantation owners.
Collection material in English.
Keywords: Craighead, James B. -- 1825-1912.; Craighead family; Craighead family -- Genealogy; Agriculture -- Arkansas -- Mississippi County; Cooking; Genealogy; Medicine -- Formulae, receipts, prescriptions; Plantations -- Arkansas -- Mississippi County; Plantation life -- Arkansas -- Mississippi County; Slavery -- Arkansas -- Mississippi County; Slaves -- Arkansas -- Mississippi County; Arkansas -- Genealogy; Arkansas -- History -- 19th century; Arkansas -- Social life and customs; Mississippi County (Ark.) -- History; Mississippi County (Ark.) -- Social life and customs; Stonewall (Ark. : Estate)